1977
DOI: 10.1002/j.1537-2197.1977.tb07600.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource Allocation and Reproduction in Populations of Amphicarpum Purshii (Gramineae)

Abstract: Five New Jersey populations of Amphicarpum purshii (an annual panicoid grass) were investigated as to total allocation of biomass to reproduction and its distribution between aerial chasmogamous and subterranean cleistogamous inflorescences. Germination of both types of seed was documented, for the first time, in not only the field but under three laboratory temperature regimes. Overall, approximately 29 % of the shoot biomass was allocated to reproduction. On a population basis, subterranean inflorescences ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 17 publications
0
22
1
Order By: Relevance
“…We also excluded estimates based on measures of the fitness of selfed and open-pollinated crosses, which can be biased by selfing in the open-pollinated crosses. Finally, we excluded comparisons of progeny from cleistogamous and chasmogamous flowers because these can be biased both by selfing in the chasmogamous flowers and by nongenetic differences in the sizes and germination behaviors of seeds produced by the two flower types (see, e.g., McNamara and Quinn 1977;Lu 2002). For each population, we recorded fitness components for up to four life-cycle stages.…”
Section: Mating System and Id: Empirical Resultsmentioning
confidence: 99%
“…We also excluded estimates based on measures of the fitness of selfed and open-pollinated crosses, which can be biased by selfing in the open-pollinated crosses. Finally, we excluded comparisons of progeny from cleistogamous and chasmogamous flowers because these can be biased both by selfing in the chasmogamous flowers and by nongenetic differences in the sizes and germination behaviors of seeds produced by the two flower types (see, e.g., McNamara and Quinn 1977;Lu 2002). For each population, we recorded fitness components for up to four life-cycle stages.…”
Section: Mating System and Id: Empirical Resultsmentioning
confidence: 99%
“…Energetic costs of chasmogamous seeds are two to three times greater than for cleistogamous seeds in Impatiens pallida and I. bifiora (Schemske, 1978). Cleistogamous seedlings are more common than chasmogamous seedlings in populations of Amphicarpum purshii (McNamara and Quinn, 1977) even though seeds are produced in roughly equal numbers.…”
Section: Percent Of Variancementioning
confidence: 94%
“…Small plants, plants lacking adequate water or light, or plants growing in dense stands may produce solely cleistogamous flowers while other plants, in better conditions, may produce predominantly chasmogamous flowers (Koller and Roth, 1964;Levin, 1972;Schemske, 1978;Waller, 1980;Weiss, 1980;Thompson and Beattie, 1981). It appears chasmogamous flower production is more plastic than cleistogamous flower production in Danthonia spicata as well, as evidenced by the lower heritability for the total number of chasmogamous flowers per plant, but Danthonia does not exhibit drastic fluctuations in the percentage of cleistogamous flowers so commonly reported in other species (Levin, 1972;McNamara and Quinn, 1977;Waller, 1980;Weiss, 1980). Cleistogamy in the grasses has been subdivided into four discrete types (Hackel, 1906); this classification was later extended to all flowering plants (Uphof, 1938).…”
Section: Percent Of Variancementioning
confidence: 98%
“…For example, in several species of Viola (Violaceae) Culver and Beattie (1978) found that seeds from cleistogamous flowers were taken by ants less frequently than seeds from chasmogamous flowers, even though seeds from cleistogamous flowers had larger elaiosomes. There are also some plant species in which the cleistogamous flowers are subterranean and their diaspores are non-dispersive, e.g., Gymnarrhena micrantha (Asteraceae) (Koller and Roth, 1964) and Amphicarpum purshii (Poaceae) (Chase, 1918;McNamara and Quinn, 1977). Schmitt et al (1985) have also shown that seeds are dispersed farther from chasmogamous capsules ofthe explosively dehiscent Impatiens capensis (Balsaminaceae) than from the cleistogamous capsules.…”
mentioning
confidence: 99%